The Psychodynamics of Top Teams and the Impact on Strategic Organisational Learning: Three Case Studies in the Public Sector - Jarrett, Michael (Cranfield University, 1998)
The growing literature on organisational change, organisational learning and the role of the top team prompted the question: what is the relationship between top teams and organisational leaming? It seemed that role of the top team was important to attain successful change and ultimately learning. Yet how this was achieved seemed to be poorly understood in the literature. Thus, the thesis focused attention on the dynamics of the top team, its organisational context and the state of the external environment to gain a clearer understanding of these relationships. In order to deepen that understanding, the thesis took a systemic and psychoanalytical approach and a clinical research methodology, which provided a different perspective and seemed to be more suited to this type of inquiry on organisational dynamics. The 'findings' from the three, in-depth, public sector case studies suggested that while the dynamics of the top team could impact negatively on the group task, its impact on strategic organisational learning was less significant. The main conclusion drawn from the study was that strategic organisational learning was impaired not so much by the top team's dynamics, but by organisational and systemic defensive routines. The source of these recursive pattems was threefold: psychodynamic ego and social defenses among top team members, within the top team's group and within the dynamics of the Board A poor 'holding environment' so that these organisational dynamics were not sufficiently contained and thus each strategic subsystem was less 'task' focused an underbounded strategic apex that reinforced the dysfunctional dynamics already in play The implication from these public sector, case studies was that while the external environment and the dynamics of the top team were not insignificant, it was the poor quality and instability of the internal organisational context that inhibited learning. The role of the Board or elected officials was particularly significant in contributing to this outcome.